Korean Popular Culture as A ‘Lethal Weapon’: A Journey Toward Nation Branding of The Republic of Korea - Abidin, Zainal; Mayasari, Mayasari; Utamidewi, Wahyu; Tayo, Yanti; Nursanti, Siti (JURNAL ILMU SOSIAL, 2024)
(Korean Popular Culture as A ‘Lethal Weapon’: A Journey Towards Nation Branding of the Republic of Korea) The crisis that occurred in 1997 was experienced by the Republic of Korea as a sign that today the Republic of Korea has become a developed country. The government of the Republic of Korea took the initiative to borrow funds from the IMF for the first time in the history of Korea. The Republic of Korea's turnaround process was revived from adversity due to the impact of the crisis, which led to a day called "National Embarrassment Day". After the funds from the IMF are in the hands of the ROK government, the next duty is to use these funds wisely to restore the economic conditions. Based on the above facts, the purpose of this research was to analyze popular culture as a process of nation branding in South Korea. The method in this research was qualitative with a case study approach, the data obtained comes from in-depth interviews, non-participant observation and literature review. This research concludes that the crisis is an initial process for the Korean government's initiative to take bold and anti-mainstream steps. The funds obtained from the IMF were used to produce popular culture, which was then used as a tool by the government and expanded to restore the country's economic condition, the government's initiative at that time brought about major changes in the current economic condition of the Republic of Korea, and popular culture became the nation branding of the Republic of Korea.